2012
DOI: 10.1007/s10886-012-0150-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Optimization of a Synthetic Milkweed Floral Attractant for Mosquitoes

Abstract: A pentane extract of flowers of common milkweed, Asclepias syriaca (Asclepiadaceae), elicited significant orientation from both male and female Culex pipiens in a dual-port flight olfactometer. Analysis of the extract by gas chromatography–mass spectrometry revealed six major constituents in order of relative abundance: benzaldehyde, (E)-β-ocimene, phenylacetaldehyde, benzyl alcohol, nonanal, and (E)-2-nonenal. Although not all were collected from the headspace profile of live flowers, a synthetic blend of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 42 publications
2
41
0
1
Order By: Relevance
“…Laboratory assays have further shown that floral and vegetative scents play a vital role in the attraction of Ae. aegypti to Asclepias syriaca (Vargo and Foster, 1982), Culex pipiens pipiens to L. vulgare , A. millefolium , Asclepias syriaca , and Solidago canadensis (Mauer and Rowley, 1999; Otienoburu et al, 2012), and An. gambiae to Parthenium hysterophorus , Ricinus communis and Bidens pilosa (Nyasembe et al, 2012).…”
Section: Sources Of Attractive Plant Odoursmentioning
confidence: 99%
See 3 more Smart Citations
“…Laboratory assays have further shown that floral and vegetative scents play a vital role in the attraction of Ae. aegypti to Asclepias syriaca (Vargo and Foster, 1982), Culex pipiens pipiens to L. vulgare , A. millefolium , Asclepias syriaca , and Solidago canadensis (Mauer and Rowley, 1999; Otienoburu et al, 2012), and An. gambiae to Parthenium hysterophorus , Ricinus communis and Bidens pilosa (Nyasembe et al, 2012).…”
Section: Sources Of Attractive Plant Odoursmentioning
confidence: 99%
“…Solvent extraction has been widely used to collect plant volatiles for elucidation of their potential attractiveness to various mosquito species, with a single solvent (Otienoburu et al, 2012) or a series of solvents (Vargo and Foster, 1982; Jepson and Healy, 1988) used to extract floral compounds of different plant species. Solvent extraction is advantageous in that it is possible to get the full volatile organic profile of the plant by varying the type of solvent used.…”
Section: Volatile Collection Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…A. curassavica was another plant species selected based on published indications of attractiveness to mosquitoes. It is related to A. syriaca, which possesses floral scents attractive to mosquitoes (Foster, 2008;Otienoburu et al, 2012) and is commonly associated with mosquitoes in the field (W.A. Foster, personal communication).…”
Section: Discussionmentioning
confidence: 99%